Formulation, optimization, and nephrotoxicity evaluation of an antifungal in situ nasal gel loaded with voriconazole‒clove oil transferosomal nanoparticles - Ahmed K. Kammoun (Taylor & Francis Group, 2021)
Fungal infections of the paranasal cavity are among the most widely spread illnesses nowadays. The aim of the current study was to estimate the effectiveness of an in situ gel loaded with voriconazole‒clove oil nano-transferosomes (VRC-CO-NT) in enhancing the activity of voriconazole against Aspergillus flavus, which causes rhinosinusitis. The nephrotoxic side effects of voriconazole may be reduced through the incorporation of the clove oil, which has antioxidant activity that protects tissue. The Box‒Behnken design was applied to formulate the VRC-CO-NT. The particle size, entrapment efficiency, antifungal inhibition zone, and serum creatinine concentration were considered dependent variables, and the soybean lecithin, VRC, and CO concentrations were considered independent ones. The final optimized formulation was loaded into a deacetylated gellan gum base and evaluated for its gelation, rheological properties, drug release profile, permeation capabilities, and in vivo nephrotoxicity. The optimum formulation was determined to be composed of 50 mg/mL lecithin, 18 mg/mL VRC, and 75 mg/mL CO, with a minimum particle size of 102.96 nm, an entrapment efficiency of 71.70%, an inhibition zone of 21.76 mm, and a serum creatinine level of 0.119 mmol/L. The optimized loaded in situ gel released 82.5% VRC after 12 hours and resulted in a 5.4-fold increase in drug permeation. The in vivo results obtained using rabbits resulted in a nonsignificant differentiation among the renal function parameters compared with the negative control group. In conclusion, nasal in situ gel loaded with VRC-CO-NT is considered an efficient novel carrier with enhanced antifungal properties with no signs of nephrotoxicity.